Strategies to Improve the Catalytic Activity and Stability of Bioinspired Cu Molecular Catalysts for the Orr - Zagal-Moya, J; Zagal-Moya, J; Venegas-Toledo, R (Elsevier B.V., 2022)
The oxygen reduction reaction (ORR) is essential for energy conversion devices such as fuel cells and metal-air batteries. The use of expensive and scarce noble metal materials to catalyze the ORR is a limitation for the massification of these energy conversion technologies. Copper molecular catalysts that mimic the active sites of metalloenzymes such as laccase are under continuous development. In this minireview, we present the strategies to increase the activity and stability of the copper catalysts for the ORR. The flexibility, lability, and electronic character of the ligands are crucial to promote the ORR. In addition, the use of polymers as backbone for multicopper catalysts and the synthesis of copper carbon-based pyrolyzed catalysts present remarkable results with promissory applications. © 2022 The Author(s)